Spółki wobec ochrony środowiska a rynek kapitałowy - Dziawgo, Leszek (Companies Attitudes of Environmental Protection and Capital Market, 2007)
On the financial market some behaviors described as CSR and SRI (Corporate Social Responsibility and Social Responsible Investment) are becoming more and more popular. For better transparency of this part of the financial market a few specific stock exchange indexes, such as DJSI and FTSE4Good were launched in the last years. In those indexes the shares of social responsible companies, and among others environmental friendly companies, were included. On the financial market there are also investment funds operating on the SRI rules. Many widely recognized capital-banking groups are engaged in such investment activities - UBS, Credit Suisse, Deutsche Bank, ING, HSBC and others. The above mentioned facts lead to the conclusions that even on the financial market ecological aspects of economy are more important than before. This could be a valuable indication for companies
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 106-114